Analisis Perbandingan Brand Equity E-Commerce Shopee Dan Lazada Di Kalangan Mahasiswa Unisma - Radha Maudyna R; Siti Asiyah; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The implementation of social restrictions during the pandemic encourages consumers to take advantage of online shopping, thereby encouraging the growth of online shopping facilities. Two brands that are known by the public are Shopee and Lazada. This phenomenon provides the basis for this research, namely to compare the brand equity of the two brands.This study aims to examine and analyze: 1) Shopee and Lazada online shopping service brand awareness, Shopee and Lazada online shopping service quality perceptions, Shopee and Lazada online shopping service brand associations, Shopee and Lazada online shopping service brand loyalty.The study used a quantitative descriptive approach with purposive sampling technique in order to obtain as many as 86 respondents. The analysis technique used paired sample t-test.The results showed that there were 1) significant differences between shopee's brand awareness compared to lazada, 2) significant differences between shopee's brand associations and lazada's, 3) significant differences between shopee's perceived quality and lazada, 4) there is no significant difference between shopee and lazada brand loyalty. Keywords : Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty